2017
DOI: 10.1371/journal.pone.0189224
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of WRKY genes and their expression profiles under different abiotic stresses in Elaeis guineensis

Abstract: African oil palm (Elaeis guineensis) is an important oil crop grown in tropical region and sensitive to low temperature along with high tolerance to salt and drought stresses. Since the WRKY transcription factor family plays central roles in the regulation of plant stress tolerance, 95 genes belonging to the WRKY family were identified and characterized in oil palm genome. Gene structure analysis showed that EgWRKY genes have considerable variation in intron number (0 to 12) and gene length (477bp to 89,167 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…There is a crucial need for efficient crop improvement strategies with novel genome editing techniques, such as CRISPR-Cas9 [69], which is easy, fast, efficient, and accurate in obtaining new genome edited crops ( Figure 5). Global warming is leading to increases in several kinds of abiotic stress, including temperature and drought, which are major abiotic stresses that limit crop production [70]. Scientists are screening to determine candidate genes using CRISPR-Cas9 technology to overcome these environmental problems.…”
Section: The Development Of Abiotic Stress-tolerant Crops By Crispr (mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a crucial need for efficient crop improvement strategies with novel genome editing techniques, such as CRISPR-Cas9 [69], which is easy, fast, efficient, and accurate in obtaining new genome edited crops ( Figure 5). Global warming is leading to increases in several kinds of abiotic stress, including temperature and drought, which are major abiotic stresses that limit crop production [70]. Scientists are screening to determine candidate genes using CRISPR-Cas9 technology to overcome these environmental problems.…”
Section: The Development Of Abiotic Stress-tolerant Crops By Crispr (mentioning
confidence: 99%
“…When considering tropical climates, Elaeis guineensis is the main source of edible oil in Africa and is very sensitive to low temperature, but resists drought and salinity well [23]. WRKY genes demonstrated tissue-specific expression under low temperature stress in oil palms [70].…”
Section: The Development Of Abiotic Stress-tolerant Crops By Crispr (mentioning
confidence: 99%
“…For example, a WRKY transcription factor that acts as negative regulator of abscissic acid signaling is crucial to up-regulate lipid remobilization during germination in sunflower [ 73 ]. A comprehensive analysis of WRKY factors in oil palm has been provided [ 74 ], and future research will likely provide more insight on differential expression during the germination of WRKY factors associated with abscissic acid and gibberellin signaling. Additionally, mitochondrial reactivation during seed imbibition has been shown to be stimulated by gibberellins and inhibited by abscissic acid in Arabidopsis [ 45 ].…”
Section: Control Of Germinationmentioning
confidence: 99%
“…It was found that EgWRKY genes of oil palm had showed tissue-specific expression patterns with higher levels under cold stress. It is now well recognized that almost all the EgWRKY genes are upregulated under abiotic stresses, and the authors suggest that the expression of EgWRKY genes in African oil palm play important roles in the responses to abiotic stresses (Xiao et al, 2017 ). Although CRISPR/Cas9 has not yet been applied for the improvement of most of the tropical crops, opportunity does exist to apply the technology for genetic modification of numerous tropical crops to increase yield and improve product quality, abiotic stress tolerance, and enhancing the resistance to destructive diseases and pests.…”
Section: Development Of Abiotic Stress Tolerant Crop Plants In the Trmentioning
confidence: 99%